"Does chest circumference affect pulmonary function tests? A comparative study of male and female subjects" - Saxena, Settings Jalaj; Rastogi, Parag; Gupta, Sushma; Saha, Saurabh; Kumar, Virendra; Saxena, Sonali (Indian Journal of Community Health, 2005)
The values of Pulmonary Function Tests PFTs help in the diagnosis of restrictive and obstructive diseases. There are various studies on various physical parameters evaluating PFTs. The present study had been planned to correlate the chest circumference in adults with PFTs, as this type of study are lesser in number. Methods ; The young subjects comprised of 119 males (18-27 years) and 49 females (18-23 years) of first professional M.B.B.S. of G.S.V.M. medical College, Kanpur. The Parameters recorded were Tidal volume (T.V.),Forced Expiratory volume in first second (FEV1), Forced vital capacity (F.V.C.), Forced Expiratory Ratio (F.E.R.) and Peak Expiratory Flow Rate (P.E.F.R.). The chest circumference of all the subjects was measured and subjects were divided in to 3 groups according to it. The statistical evaluation was done by 'Students's 't'-test and p < 0.05 was taken as signifcant. Results : The mean T.V., FEV1, F.V.C, F.E.R. and P.E.F.R were 437.56 +- 65.83 ml, 3.26 +- 0.41 L, 3.82 +- 0.48L, 85.09 +- 2.42% and 495.42 +- 101.82 L/min respectively in North Indian male suibjects, between mean age of 18 - 27 years. The average T.V., FEV1, F.V.C., F.E.R, and P.E.F.R, were 386,12 +- 37.90 ml, 2.39 +- 0.38L, 2.79 +- 0.43L, 85.38 +- 2.57 % and 307.12 +-75.74 L/min respectively in North Indian Female subjects, between mean age of 18 - 23 years. Conclusion: The chest circumference in the same sex in all the three subgroups do not affect the values of PFTs after adulthood i.e. more than 18 years of age. The Gender variation between males and females do affect the various values of PFTs.